Management of Qur’anic Memorization Learning at Al Falah Darussalam Tropodo Islamic Elementary School: Pengelolaan Pembelajaran Hafalan Al-Qur’an di Sekolah Dasar Islam Al Falah Darussalam Tropodo - Zuhroh, Siti Fatimatuz; Fahyuni, Eni Fariyatul (Indonesian Journal of Innovation Studies, 2026)
General Background Qur’an memorization programs have expanded rapidly within Islamic primary education. Specific Background However, primary schools frequently face challenges in maintaining long-term educational quality due to unstructured management systems and unstandardized evaluations. Knowledge Gap Existing studies mainly focus on memorization techniques or short-term outcomes rather than comprehensive managerial frameworks. Aims This study analyzes the planning, organizing, actuating, and controlling functions of Qur’an memorization management, along with its institutional opportunities and challenges. Results A qualitative case study reveals that structured management featuring regular and specialized takhassus classes, supported by a tiered evaluation system, yields consistent memorization completion rates. Novelty The findings demonstrate that combining program differentiation with multi-tiered controlling mechanisms creates a scalable, structured model for elementary Islamic institutions. Implications Institutional commitment and active parental involvement serve as essential catalysts for sustaining high-quality memorization outcomes in primary education. Key Findings Highlights Structured management with differentiated learning streams drives consistent memorization achievement. Tiered evaluation mechanisms ensure systematic tracking and sustained learning quality. Institutional leadership combined with active parental involvement strengthens program sustainability. Keywords : Learning Management, Qur'an Memorization, Islamic Elementary School, Takhassus Class, Educational Evaluation